Agriculture in the Islamic Economic System: Prophetic Guidance and Developmental Measures - Mazhar Hussain; Dr. Manzhoor Ahmed Al-Azhari (Journal of Religion and Society, 2025)
This research article offers a rigorous and comprehensive examination of the significance, status, and multidimensional role of agriculture within the Islamic economic system. Drawing upon the Qur’an, the Sunnah of the Prophet Muhammad (ﷺ), classical juristic sources, and the practical experiences of Islamic history, the study seeks to establish that agriculture in Islam is not merely a productive or economic activity. Rather, it constitutes a fundamental pillar of social justice, human sustenance, moral responsibility, and state self-sufficiency. The article further elucidates that, within Islamic thought, the interdependent relationship between land, water, and human labor transcends material considerations and embodies profound religious, ethical, and spiritual dimensions. The study demonstrates that Qur’anic references to land, sustenance, and agricultural production are embedded within a divinely ordained system, thereby directly linking human livelihood to divine providence. The Prophetic Sunnah provides robust practical endorsement of agricultural activity through emphases on tree plantation, the exceptional virtue of reviving barren land (ihyāʾ al-mawāt), the promise of ownership and reward, and the recognition of agricultural labor as an act of worship. These principles collectively form the conceptual foundation of Islamic agricultural thought. Furthermore, the article presents a critical and contextual analysis of the narration attributed to Abū Umāmah al-Bāhilī, which has sometimes been interpreted as disparaging agricultural engagement. It clarifies that this narration addresses a specific mindset in which excessive preoccupation with material pursuits leads to neglect of religious obligations, collective responsibilities, and jihad; agriculture itself, however, remains intrinsically virtuous and commendable. The article further underscores that the defining characteristic of the Islamic economic system lies in its principle of moderation and balance, wherein agriculture, trade, and defense obligations are organically interconnected. Historical case studies from al-Andalus and the Ottoman Caliphate clearly illustrate that when agricultural prosperity becomes detached from ethical values and religious consciousness, material affluence may itself serve as a precursor to decline. Conversely, when agricultural practices are governed by the objectives of Sharīʿah and the principles of social justice, the sector emerges as a powerful foundation for economic stability and societal well-being. Moreover, the study conceptualizes the Islamic agricultural framework based on zakāt and ʿushr as an effective welfare-oriented model that curtails wealth concentration and contributes to poverty alleviation. Islamic injunctions advocating moderation and prohibiting the waste of natural resources further demonstrate that Islamic agricultural thought is inherently compatible with contemporary principles of sustainable agriculture. In conclusion, the article argues that in the contemporary era—particularly in agrarian states such as Pakistan—agricultural policies grounded in Prophetic principles provide a comprehensive and viable framework for achieving food self-reliance, environmental sustainability, and economic sovereignty. Thus, the Islamic agricultural system is not merely a historical or traditional construct but a coherent and practical response to both present and emerging economic challenges۔ Keywords:Islamic Economic System, Agriculture in Islam, Sunnah of the Prophet ﷺ, Agricultural Development, Food Security and Ushr